Monetary policy and the redistribution channel in the euro area - Atanas Pekanov (Austrian Institute of Economic Research (WIFO), 2024)
Monetary policy has implicit redistribution effects for households when households are different. This changes the aggregate consumption response to interest rate changes. This paper is the first to estimate the magnitude of redistributionary channels of monetary policy in the euro area. When households have heterogeneous MPCs and balance sheets, three redistributionary channels amend the standard consumption response to monetary policy - an earnings heterogeneity channel, an inflation-driven Fischer channel and a real interest rate channel. I construct a new dataset combining the ECB HFCS and the Eurostat HBS to obtain a representative euro area dataset with detailed information on household balance sheets and consumption. I use a unique question in the HFCS to calculate the sufficient statistics necessary to evaluate these redistribution channels. For the euro area the three redistribution channels enhance monetary policy - the effects of one time expansionary monetary policy shocks in stimulating consumption are stronger than in models without heterogeneity. In the euro area, a 1 percent decrease in the real interest rate redistributes wealth from creditors to debtors, and creates further income and price effects. This increases aggregate consumption through unequal exposure to interest rate changes, the price level and earnings respectively by 9 basis points, 7 basis points and another 2 basis points. Redistribution amplifies the monetary policy change and makes the aggregate consumption response 15 percent higher. The relative power of different channels of monetary policy is revised from the standard model - the redistribution channel with household heterogeneity makes up 14 percent of the total consumption response, while the aggregate demand and the substitution channel amount to respectively 53 and 33 percent. When households earnings react unequally to GDP changes, as estimated in the data, their heterogeneous individual earnings elasticities enhance this effect further and the share of the redistribution channel of earnings heterogeneity increases to between 20 and 27 percent. With heterogenous earnings elasticities redistribution amplifies the effects of monetary policy by up to 37 percent.
Keywords: D31; D52; E21; E52; 330; MPC; Household balance sheets; Monetary policy transmission; Consumption Dynamics; Redistribution